Impacts of Hurricane Damage on Southern Highbush Blueberries - Doug Phillips; Jeffrey Williamson; Philip Harmon (EDIS)
This publication discusses the types of hurricane damage that can be incurred in blueberry production operations, the impacts of these damages, preparations to make before the storm arrives, and suggestions on best management practices in the aftermath of a storm.